2018
DOI: 10.1128/jb.00345-18
|View full text |Cite
|
Sign up to set email alerts
|

Redirection of Metabolism in Response to Fatty Acid Kinase in Staphylococcus aureus

Abstract: is capable of phosphorylating exogenous fatty acids via the fatty acid kinase FakA for incorporation into the bacterium's membrane. Additionally, FakA plays a significant role in virulence factor regulation and skin infections. We previously showed that a mutant displays altered growth kinetics observed during late-exponential phase of growth. Here, we demonstrate that the absence of FakA leads to key metabolic changes. First, the mutant has an altered acetate metabolism with acetate being consumed at an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 56 publications
1
28
0
Order By: Relevance
“…This may be due to the pleiotropic phenotype ascribed to USA300 ΔfakA, including an elevated pool of nonesterified fatty acids, leading to reduced transcription of the SaeRS two-component regulator and defective production of Hla toxin (32)(33)(34). Broader metabolic changes were also noted, including altered carbon and amino acid metabolism (35). An elevated basal expression of farE in response to accumulation of cellular metabolites would be consistent with observations that other RND family efflux pumps also exhibit increased expression in response to an accumulation of cellular metabolites (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the pleiotropic phenotype ascribed to USA300 ΔfakA, including an elevated pool of nonesterified fatty acids, leading to reduced transcription of the SaeRS two-component regulator and defective production of Hla toxin (32)(33)(34). Broader metabolic changes were also noted, including altered carbon and amino acid metabolism (35). An elevated basal expression of farE in response to accumulation of cellular metabolites would be consistent with observations that other RND family efflux pumps also exhibit increased expression in response to an accumulation of cellular metabolites (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…FakA, along with its lipid binding partners, phosphorylates free fatty acids and is essential for both incorporation of exogenous fatty acids and fatty acid turnover [ 18 , 34 ]. It was recently reported that its inactivation alters acetate metabolism by an unknown mechanism [ 35 ], which would explain its occurrence in the screen as favoring the redirection of acetyl-CoA flow towards acetate production rather than SCFA. The ltaS gene encodes the lipoteichoic acid synthetase responsible for lipoteichoic acid (LTA) synthesis [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…aureus [ 34 ]. A recent report and particularly interesting study in light of our own showed that inactivation of fakA impacts the acetate switch, resulting in high secretion of acetate during exponential growth [ 35 ]. We can thus propose that fakA mutations help ΔcshA growth through the redirection of acetyl-CoA flow away from SCFA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…FakA depletion leads to free fatty acid accumulation that may modify S . aureus regulation and FASII activity and alter acetate utilization [ 5 , 6 ]. How the slowdown of FASII synthesis adjusts fatty acid membrane composition and fluidity is a new open question arising from this work.…”
Section: Why Are Fasii Genes Targets For Csha Suppmentioning
confidence: 99%